Barriers to Export for Export Firms in Myanmar After 2021: Evidence from Firm-Level Analysis - Atar Thaung Htet; Htin Kyaw Lin (Research Synergy Press, 2025)
This study intends to analyze the effect of export barriers on the export performance of export firms in Myanmar after the 2021 military coup. There are two specific objectives for this study. The first one is to analyze the effect of internal barriers on export performance, and the second one is to examine the effect of external barriers on export performance. This study used primary and secondary data to achieve the research objectives. The primary data was obtained by the survey method. The 130 respondents who are owners and senior/mid-level managers of 70 exporting firms participated in this research. A stage sampling method was applied for primary data. The World Bank data site provides the secondary data for this study. This research extracted the data from 2011 to 2023 as the basic time frame for the study period. The descriptive statistical analysis and multiple linear regression analysis method were applied as major data analysis techniques in this study. The research found that informational barriers and functional barriers have a significant effect on the export performance of export firms in Myanmar on the internal barriers side. On the other hand, macro factor barriers and procedural barriers have positively positive effect on export performance. The study suggested that policymakers of Myanmar should align the macroeconomic policies by reflecting the real trade situation. At the firm level, individual firms should emphasize their export strategies that are relevant in the regional and the rest of the world. Moreover, the study suggests to the academic world for further exploration in the research field of export barriers and export performance in the context of developing countries.